Do Easterners and Westerners Differ in Visual Cognition? A Preregistered Examination of Three Visual Cognition Tasks. (March 2017) - Hakim, Nicole; Simons, Daniel J.; Zhao, Hui; Wan, Xiaoang
When performing cognitive tasks, Easterners often process information more holistically and contextually than Westerners. This is often taken as evidence for fundamental differences in basic cognition, including attention and perception. Yet, evidence for such basic cognitive differences is inconsistent, many studies are based on small samples, and few have been replicated. We report a preregistered replication of three prominent findings of cultural differences in visual cognition, testing a substantially larger sample than the original studies. Our comparisons of American and Asian International students living in the United States provided relatively little evidence for robust and consistent cultural differences in global/local biases, relative and absolute length judgments, or change detection performance. Although we observed some differences in change detection performance when comparing Chinese to American students, those differences were inconsistent across measures. We discuss the need for larger scale replications that adequately control for the testing context and demand characteristics.